Enhancing Student Learning in Knowledge-Based Courses: Integrating Team-Based Learning in Mass Communication Theory Classes. (June 2014) - Han, Gang (Kevin); Newell, Jay
This study explores the adoption of the team-based learning (TBL) method in knowledge-based and theory-oriented journalism and mass communication (J&MC) courses. It first reviews the origin and concept of TBL, the relevant theories, and then introduces the TBL method and implementation, including procedures and assessments, employed in an undergraduate mass communication theory class in a large Midwest research university. Students showed significantly improved group knowledge versus individual knowledge over an entire semester through readiness assurance tests (RAT), which were also demonstrated in a pre–post survey and two peer evaluations. The significance of this study concerning students' learning effectiveness and outcomes as well as its pedagogical implications for the J&MC field and beyond are discussed.